The Problem of Environmental Democracy: Responsibility and Deliberation - Pommier, Éric (Environmental ethics, 2019)
The work of Hans Jonas’ has been largely overlooked by environmental philosophers. His Principle of Responsibility can help guide effective development of political institutions for environmental purposes. It is possible to use this principle to develop a deliberative and environmental conception of democracy. Some implications of the social contract framework of deliberative democracy show that Jonas’ conceptualization of responsibility leads to an environmental and deliberative conception of democracy by accommodating different citizens’ senses of the good in terms of an environmentally conceived global governance.